Bistability and Bursting Oscillations in Electromechanical Butterfly Valves - Kwuimy, C.A. Kitio; Nataraj, C. (Journal of Applied Nonlinear Dynamics, 2026)
This papers considers an electromechanical butterfly valve and discusses the conditions for appearance of bistability and bursting oscillations. The critical nonlinear stiffness coefficient and inlet velocities leading to such dynamics are obtained as a function of the system parameters, and the effects of external perturbation on the bursting response of the system are illustrated. It is observed that the driving parameters and the direct current voltage strongly affect the sharpness, the number of strikes, the amplitude of the strikes and the time interval between the strikes. Combinations of large-amplitude oscillations and small- amplitude oscillations are obtained for the electric circuit, while combination of fast-slow dynamics is obtained for the mechani- cal part. The results of the paper provide potential criteria for evaluating and optimizing system performance.